2019
DOI: 10.1055/a-0999-0149
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Hydrogen Sulfide Alleviates-Induced Intracellular Inflammation in HepG2 Cells

Abstract: Fatty acids induced hepatic inflammation plays an important role in nonalcoholic fatty liver disease (NAFLD) pathogenesis. Hydrogen sulfide (H2S), an endogenous gasotransmitter, has been established to possess potent anti-inflammation in various human organs. However, the anti-inflammation property of H2S in the fatty liver is still needed to further elucidate. Hence, this study aimed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Exogenous H 2 S donors are reported to protect HepG2 hepatocytes against palmitic acid-induced inflammation, implying that the H 2 S system may be a crucial target for the treatment of NAFLD through its anti-inflammatory effects [124] . The hepatic H 2 S levels, CBS and CSE expressions are impaired in rats with NASH induced by a methionine/choline-deficient diet, and treatment with exogenous H 2 S prevents the progression of NASH possibly through suppression of liver oxidative stress and inflammation [125] .…”
Section: Role Of H 2 S In Non-alcoholic Fatty Livementioning
confidence: 99%
“…Exogenous H 2 S donors are reported to protect HepG2 hepatocytes against palmitic acid-induced inflammation, implying that the H 2 S system may be a crucial target for the treatment of NAFLD through its anti-inflammatory effects [124] . The hepatic H 2 S levels, CBS and CSE expressions are impaired in rats with NASH induced by a methionine/choline-deficient diet, and treatment with exogenous H 2 S prevents the progression of NASH possibly through suppression of liver oxidative stress and inflammation [125] .…”
Section: Role Of H 2 S In Non-alcoholic Fatty Livementioning
confidence: 99%
“…Although H 2 S, a small molecule that is traditionally conceptualized as toxic, can exhibit neurotoxicity and reduced cell survival at higher concentrations [25], it was reported that in microglia (Microglial), high concentrations of H 2 S can increase cellular ROS [26]. The high concentrations of NaHS in HepG2 cells counteracts the anti-in ammatory effect at low concentrations In HepG2 cells, high concentrations of NaHS counteracted the anti-in ammatory effect at low concentrations of NaHS [27]. And at lower concentration condition, H 2 S showed positive effects on different diseases, mainly re ecting from in ammatory responses [27; 28; 29].…”
Section: Discussionmentioning
confidence: 99%
“…S9, ESI †). DCH-S is lack of sensitivity to pH with a wide range (2)(3)(4)(5)(6)(7)(8)(9)(10)(11). However, by studying the pH effect, DCH-S was found to respond to NaHS and show obvious fluorescence enhancement in the pH range of 5-9.…”
Section: Optical Response Of Dch-s To H 2 Smentioning
confidence: 99%
“…[3][4][5] The endogenously produced H 2 S was found to participate in the regulation of numerous physiological and pathological processes such as neurotransmission, vasodilation, angiogenesis, apoptosis, antioxidation and anti-inflammation. [6][7][8][9][10][11][12] It has also been revealed that abnormal levels of H 2 S is associated with Alzheimer's disease, Down's syndrome, diabetes, and many other diseases. [13][14][15][16][17][18][19] For a better understanding of the complex performance of H 2 S in diverse physiological events as well as pathology of diseases, considerable attention has focused on the accurate and efficient methods to analyze H 2 S in biological systems.…”
Section: Introductionmentioning
confidence: 99%